2018
DOI: 10.1038/s41564-018-0225-4
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies cross-feeding orchestrates carbon degradation in the rumen ecosystem

Abstract: Because of their agricultural value, there is a great body of research dedicated to understanding the microorganisms responsible for rumen carbon degradation. However, we lack a holistic view of the microbial food web responsible for carbon processing in this ecosystem. Here, we sampled rumen-fistulated moose, allowing access to rumen microbial communities actively degrading woody plant biomass in real time. We resolved 1,193 viral contigs and 77 unique, near-complete microbial metagenome-assembled genomes, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
148
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 71 publications
12
148
1
2
Order By: Relevance
“…The concept of trophic levels has been widely used in macro-ecosystems to make sense of flow 269 of nutrients and energy in large food webs [24,25,26], but it has only received limited attention 270 in microbial ecosystems, one example being ref. [27]. There is no absolute consensus definition 271 of a trophic level with several interpretations discussed in Refs.…”
mentioning
confidence: 99%
“…The concept of trophic levels has been widely used in macro-ecosystems to make sense of flow 269 of nutrients and energy in large food webs [24,25,26], but it has only received limited attention 270 in microbial ecosystems, one example being ref. [27]. There is no absolute consensus definition 271 of a trophic level with several interpretations discussed in Refs.…”
mentioning
confidence: 99%
“…In accordance with recent research efforts to elucidate the role of the rumen virome, a significant portion of the RUS-refDB proteins (switchgrass: 56; rumen fluid: 62) were assigned to the 913 viral scaffolds we recovered from our switchgrass-associated rumen metagenome 31,56 . Recent studies have demonstrated that some viruses contribute to polysaccharide degradation directly, as they encode glycoside hydrolases 57 , or indirectly through infection of carbohydrate-degrading microorganisms 5 . Accordingly, when mining the genomic content of the viral scaffolds, we identified CAZyme domains within 444 proteincoding genes (Supplementary Figure S3).…”
Section: Virome Activity In Ruminant Biomass-degradationmentioning
confidence: 99%
“…Over the last decade, targeted efforts to isolation and cultivate novel rumen microorganisms have resulted in a more detailed understanding of the physiology of anaerobic rumen archaea and bacteria and their contribution to the overall function of the rumen ecosystem 6 . Recent studies have also shed light on the viral rumen population and although work in this area is still nascent, it suggests that the rumen virome modulates carbon cycling within the rumen ecosystem through cell lysis or re-programming of the metabolism of the host microbiome 5,7,8 . Anaerobic rumen ciliate protozoa and fungi have largely remained recalcitrant to both cultivation and molecular exploration efforts 9 , and although recent cultivation efforts have provided important insight into the lifestyle and enzymatic capacity 4,10 , their quantitative metabolic contributions to the greater rumen ecosystem are still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the correct conclusion would be that one more abundant population exists across all samples ( Figure 1). This issue has been acknowledged in multiple studies, and authors have chosen varying cutoffs to avoid this issue (e.g., >95% average nucleotide identity (Almeida, 2019); >98% average nucleotide identity (3,17), >95 % amino acid identity (18), >99.5% amino acid identity (4)).…”
mentioning
confidence: 99%